1999
DOI: 10.1542/peds.103.2.446
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in the Extremely Low Birth Weight Infant

Abstract: Infection of the amniotic fluid leading to pneumonia was the major cause of death in the extremely low birth weight infant. Accurate cause of death can not be reliably ascertained without an autopsy accompanied by examination of the placenta in the early deaths. Antibiotic treatment of the mother and infant may have reduced the deaths from infection. Early failure to respond to neonatal intensive care may well indicate presence of a congenital pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
1
10

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 27 publications
4
74
1
10
Order By: Relevance
“…In one report of autopsy data of ELBW infants, 61% of infections diagnosed at necropsy were not diagnosed before death. 51 Other complicating factors include maternal antimicrobial therapy before birth as well as the low blood volume often collected for these cultures. 52 In one recent study there was a 60% false-negative culture rate if <4 CFU of bacteria were present per ml and if <0.5 ml of blood was collected.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…In one report of autopsy data of ELBW infants, 61% of infections diagnosed at necropsy were not diagnosed before death. 51 Other complicating factors include maternal antimicrobial therapy before birth as well as the low blood volume often collected for these cultures. 52 In one recent study there was a 60% false-negative culture rate if <4 CFU of bacteria were present per ml and if <0.5 ml of blood was collected.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Improvements in survival have made it necessary to investigate causes of death other than immaturity for the infant of BW <751 g. For example, amniotic fluid infection can be responsible for premature delivery and for death of the infant due to congenital pneumonia. 43 A recent study of causes of death from our hospital that included infants from period 4 has shown that congenital infection as a cause of death in the ELBW infant peaked at GA 24 weeks and between BW 600 and 700 g. 44 Hack and Fanaroff 28 are the only authors to report survival data who also present causes of death for infants of BW <751 g. They found 34% of the deaths of these extremely premature infants due to amniotic fluid infection syndrome, compared to 27% in our study of ELBW infants. Without autopsy and study of the placenta, these deaths would likely be attributed to immaturity or RDS rather than infection.…”
mentioning
confidence: 98%
“…Nas instituições estudadas, uma das causas mais freqüentes de morte foi justamente a sépsis neonatal, nos períodos tanto da mortalidade precoce, quanto da tardia. A melhor avaliação para a corioamnionite é o estudo da placenta, como foi mostrado por Barton et al 37 . O estudo anatomopatológico da placenta quando da necrópsia não foi uma prática de rotina nas maternidades estudadas.…”
Section: Discussionunclassified
“…Um estudo concomitante revelou que a maior causa de mortalidade foi a sépsis neonatal, podendo ser a pneumonia o fator que estaria interagindo com o efeito do surfactante pulmonar. É prová-vel que os recém-nascidos de muito baixo peso que não respondem à terapêutica e vão a óbito nas primeiras horas de vida sejam casos de pneumonia congênita 37 . Haveria necessidade de outros estudos para a confirmação da associação entre a não-resposta ao uso do surfactante e a sépsis/pneumonia neonatal.…”
Section: Discussionunclassified